Risco é notícia? A relevância jornalística dos riscos nos grandes desastres da mineração brasileira - Souza, Elise Azambuja (2023)
We propose to comprehend how journalism deals with disaster risks in the context of the risk society (BECK, 2016) and precisely in the Brazilian scenario, where indicators of situations of risks are related to circumstances of vulnerability (VALENCIO; VALENCIO, 2017). We start from the perception that the news is a set of social constructions of reality that follow certain ritualistic standards of elaboration based on criteria of newsworthiness, allowing relevance to events (WOLF, 2009; TRAQUINA, 2005; SILVA, 2014), and that journalists are part of a interpretive community with its own cultural ways of perceiving the world and denoting meaning to events (ZELIZER, 200; TRAQUINA, 2005). Concerning the risks, we understand that they are not recognized by all people and groups in the same way (SLOVIC; WEBER, 2002; SJÖBERG et al., 2004; LIMA, 1995) and tend to receive a certain degree of opacity in society. Considering the idea that reporting events that have not taken place yet is not part of journalistic culture and its criteria for newsworthiness, our main objective is to point out the performance and role of journalism towards the risks as socially invisible facts. Therefore, we analyzed periods before and after two major Brazilian mining disasters, understood from the perspective of the event (QUÉRÉ, 2005). We used Content Analysis Method (BARDIN, 2016) to analyze how risks related to mining dams appear in the coverage of the em.com.br portal in the year before and the year after the dam failures that occurred in Mariana and Brumadinho, both cities in the state of Minas Gerais, totaling four periods analyzed. We observe the relevance that journalism attaches to risks over periods and their respective contexts. We realized that there is a developing relevance of risks, with emphasis on the periods after the occurrence of disasters. We conclude that risks are part of a continuous line in which events emerge and accumulate new issues on focus and the relevance of the theme for journalism is directly proportional to their perception. In the same way that risks are unveiled, inaugurated and more noticeably perceived in the context of disasters, they tend to appear in journalism associated with crisis coverage.